PERLINDUNGAN HUKUM TERHADAP HAK-HAK PEKERJA/BURUH USIA PENSIUN ATAS PESANGON, PENGHARGAAN MASA KERJA, DAN PENGGANTIAN HAK DI JAWA TIMUR - Akhmad Soleh (Legal Spirit, 2018)
Up to the present, the Law on Employment has not regulated firmly and clearly the retirement age limit of workers/labors. Therefore, although the protection of the labors’ rights have been regulated in such a way in the regulation, but it has not been able to give a complete protection to the workers/labors. The results of the present research are as follows: the legal protection to the workers/labors’ rights, viewed from the Constitution, is that the state intends to provide welfare to its people, but in the context of the Law no. 13 year of 2003 no clear retirement age limit of workers/labors is clearly stated. At the levels of policies under the law such as PK, PP, or PKB, some do not regulated it further. Therefore, labor unions should play their roles to make further regulation about the matter. On the other hand, supervision over workers/labors is inadequate since it is done by the province. Due to this problem, the Law No. 13 Year of 1003 on Employment should be revised by including the determination of the retirement age limit in order to protect them. Key words: Legal protection, Workers/labors, Retirement age